STUDI TEGANGAN LEWAT DENYAR, ARUS BOCOR DAN SIFAT HIDROFOBIK PERMUKAAN ISOLATOR KERAMIK PASANG LUAR DENGAN PELAPIS CAMPURAN KALSIUM KARBONAT DAN KARET SILIKON PADA KONDISI PENGOTORAN BUATAN - , BRIAN BRAMANTYO SATRIAJI DWI ADIPUTRO HARSONO, Prof. Dr. Ir. Hamzah Berahim, M.T. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Outdoor ceramic insulator has certain wet or dry flashover voltage value which shouldnât be surpassed during its service in electrical power transmission and distribution. The more pollutant on the insulator surface, the higher surface leakage current will be which made the wet or dry flashover voltage value of certain outdoor ceramic insulator is surpassed. One of the common treatments for outdoor insulator against pollutant is performing silicon rubber (SiR) coating in order to enhance surface hydrophobic property. Unfortunately, under prolong heavy pollutant exposure, silicon rubber (SiR) hydrophobic property will decay. This experiment purpose is to find out the influence of calcium carbonate/CaCO3 filler in silicon rubber (SiR) coating. Based on the result of experiments using 7,5 kV outdoor ceramic insulators over various artificial pollutants, C-4 coating (SiR 70% and CaCO3 30%) gives higher flashover voltage over 55,35% from 20,344 kV to 31,605 kV with lower surface leakage current over 69,12% from 2,55 mA to 0,78 mA. Equivalent Salt Density Deposit (ESDD) value is decreased over 67,86% from 25,15 mg/cm2 to 8,08 mg/cm. The hydrophobic property enhancement of C-4 coating was proven with its contact angle value 105.060 (right) and 107.870 (left) compared to pure silicon rubber (93,750 right and 92.860 left).